Identity, Integrity, and Religious Doubt in Later Life. (17th December 2021) - Clark, Phoebe; Iwasaki, Michiko; Thompson, Edward; Futterman, Andrew
Abstract: Erik Erikson argued that for religiously involved individuals, the resolution of two stages – Identity vs. Role Diffusion and Integrity vs. Despair – are of critical importance in adult development. Adults typically confront their parents' religious affiliation in adolescence and young adulthood as they establish themselves as independent actors in the world, and in later life, older adults confront their own lived lives, and evaluate in light of their religious commitments whether they have lived meaningfully and with integrity. To examine Erikson's views of religious development, we completed open-ended interviews of 278 community-dwelling older adults (55-101 years). In these interviews, participants describe the development of their religious faith, the nature and development of their religious questioning and doubt, and the relationship between their faith and doubt over their life span. Participants were from Northeast U.S., and were denominationally, racially, and ethnically diverse. More extensive religious doubts were reported during young adulthood regarding the meaningfulness of religion in their family of origin. By contrast, religious doubts are reported less during later life, and more emphasis is placed on the value of religious involvement for themselves and their families. This pattern varies between young-old (under 75 years) and old-old (over 76 years): whereas the young-old seem to be working through their religious doubts, the old-old are more focused on the value of their religious faith. These findings are discussed in terms of Erikson's developmental theory and with respect to cohort differences in religious belief and practice.